Evaluating the Normative Boundaries of Religious Moderation in Tafsir Moderasi Beragama through Muhammad Shahrur's Theory of Limits - Ahmad Mohammad Tidjani; Ahmad Mahfud; Zulfatul Wasilah; Aufal Muhammad Safii (Universitas Muhammadiyah Surakarta, 2026)
Purpose - Despite increasing scholarly attention to religious moderation in Muslim-majority societies, there remains a lack of studies that systematically evaluate the normative boundaries of state-produced Qur'anic exegesis through an internally Islamic theoretical framework. This study aims to examine how the principles of religious moderation articulated in the Indonesian Ministry of Religious Affairs' Tafsir Moderasi Beragama can be understood through Muhammad Shahrur's Theory of Limits (Naẓariyyat al-Ḥudūd), and to assess whether the text represents doctrinal flexibility or a coherent theological framework of wasaṭiyyah. Design/methods/approach - This study employs a qualitative descriptive-analytical approach based on library research. The primary source is the Ministry of Religious Affairs' Tafsir Moderasi Beragama, while Muhammad Shahrur's Theory of Limits serves as the analytical framework. Four key principles of religious moderation—justice and balance (al-'adālah wa al-tawāzun), amar ma'ruf nahi munkar, ease in religion (taysīr), and gradualism (tadarruj)—were analyzed to identify their normative upper (ḥadd al-a'lā) and lower (ḥadd al-adnā) limits. Findings - The analysis demonstrates that all four principles operate within clearly defined normative boundaries. Justice and balance are positioned between extremism and negligence, amar ma'ruf nahi munkar between moral responsibility and coercion, ease in religion between rigidity and permissiveness, and gradualism between ideal norms and social realities. These findings indicate that the Ministry's interpretation institutionalizes moderation as a structured theological paradigm rather than as doctrinal leniency. Research implications/limitations - The study is limited to a textual analysis of one official Indonesian tafsir and does not examine its reception or implementation in broader social contexts. Consequently, the findings may not be directly generalizable to other state-sponsored interpretations without comparative investigation. Originality/value - This study offers a novel application of Shahrur's Theory of Limits as an evaluative framework for official religious exegesis. It contributes a methodological model for comparative studies of state-produced religious texts and provides insights for policymakers, scholars, and practitioners seeking to promote religious moderation in pluralistic societies.